Sustainable Community Development Step 3: Create a Community Vision and Develop a Roadmap - Mickie E. Swisher; Sandra Rezola; James Sterns (EDIS)
This document presents information on developing a design to create a sustainable community. The design process, also known as a charrette, is divided into three parts. This document also includes a community planning visioning exercise. This document is FCS7216-Eng, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville FL 32611. First published: September 2003.